Tailoring the Acidity of Liquid Media with Ionizing Radiation: Rethinking the Acid-Base Correlation beyond pH - Fritsch, Birk; Körner, Andreas; Couasnon, Thaïs; Blukis, Roberts; Taherkhani, Mehran; Benning, Liane G.; Jank, Michael; Spiecker, Erdmann; Hutzler, Andreas (Journal of Physical Chemistry Letters, 2023)
Advanced in situ techniques based on electrons and X-rays are increasingly used to gain insights into fundamental processes in liquids. However, probing liquid samples with ionizing radiation changes the solution chemistry under observation. In this work, we show that a radiation-induced decrease in pH does not necessarily correlate to an increase in acidity of aqueous solutions. Thus, pH does not capture the acidity under irradiation. Using kinetic modeling of radiation chemistry, we introduce alternative measures of acidity (radiolytic acidity π* and radiolytic ion product KW*), that account for radiation-induced alterations of both H+ and OH- concentration. Moreover, we demonstrate that adding pH-neutral solutes such as LiCl, LiBr, or LiNO3 can trigger a significant change in π*. This provides a huge parameter space to tailor the acidity for in situ experiments involving ionizing radiation, as present in synchrotron facilities or during liquid-phase electron microscopy.
CRIS-Team Scopus Importer:2023-06-30